Fungal Diversity Analysis of Grape Musts from Central Valley-Chile and Characterization of Potential New Starter Cultures - Cubillos-Riffo, F; Mardones-Opazo, W (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Autochthonous microorganisms are an important source of the distinctive metabolites that influence the chemical profile of wine. However, little is known about the diversity of fungal communities associated with grape musts, even though they are the source of local yeast strains with potential capacities to become starters during fermentation. By using internal transcribed spacer (ITS) amplicon sequencing, we identified the taxonomic structure of the yeast community in unfermented and fermented musts of a typical Vitis vinifera L. var. Sauvignon blanc from the Central Valley of Chile throughout two consecutive seasons of production. Unsurprisingly, Saccharomyces represented the most abundant fungal genus in unfermented and fermented musts, mainly due to the contribution of S. uvarum (42.7%) and S. cerevisiae (80%). Unfermented musts were highly variable between seasons and showed higher values of fungal diversity than fermented musts. Since microbial physiological characterization is primarily achieved in culture, we isolated nine species belonging to six genera of fungi from the unfermented must samples. All isolates were characterized for their potential capacities to be used as new starters in wine. Remarkably, only Metschnikowia pulcherrima could co-exist with a commercial Saccharomyces cerevisiae strain under fermentative conditions, representing a feasible candidate strain for wine production. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.